Le procès et l'exécution des disciples de Jésus dans le Talmud de Babylone (B. Sanhédrin 43a) - Murcia, Thierry (Judaïsme ancien, 2013)
Immediately after Jesus' execution, the Bavli - Tractate Sanhedrin 43a in uncensored editions - relates the trial and the execution of his five disciples: Mattaï, Naqaï, Netser, Boni and Todah. I state that the text is a fictional story of late composition and I discuss the relevance of the various assumptions which have already been proposed by several scholars to explain these different names, the number five and the meaning of the whole document. I also show that the subtle and sophisticated dialogue between the disciples and the Sages - exchange of puns and biblical verses - reflects the discussions between Jews and Christians in later Babylonia. Last but not least, I reach the conclusion that the formula which introduces the episode: Yeshu had five disciples, and which is given in the Talmud as a baraita (i.e. a tannaitic dictum), is nothing but a transferring of a mishnaic formula originally related to Yohanan Ben Zakkai. Thus, the incipit gives us the tone: all this passage is a parody. On the one hand Jesus is ironically presented - in this document - as an anti-Ben Zakkai (who had five disciples). But, on the other hand and more surprisingly, he is also presented as the new Balaam (who had five assessors).